Epistemological beliefs and classroom practices of experienced physics teachers: are they related? - Sengul, Ozden (Frontiers in Education, 2024)
There is a need in teacher education to explore experienced physics teachers' domain-general epistemological beliefs and classroom practices. The study reports 30 experienced physics teachers' epistemological beliefs and classroom practices in Turkish public high school context. The data was collected through interviews and classroom observations. During the analysis, qualitative data was analyzed through constant comparative method. Level and frequency of participants' epistemological beliefs and classroom practices were quantified for descriptive statistics. The results indicated that most teachers held transitional epistemological beliefs, but they taught in traditional ways. Their epistemological beliefs and classroom practices were not in alignment. These results showed that experienced teachers might have sophisticated epistemological beliefs, but they were not able to reflect their beliefs into practice according to their perception of students' expectations. The study provides implications for research for teacher learning and development through large-scale longitudinal studies and to understand the factors of misalignment between their beliefs and practices.